Productivity and industrial growth : the Irish experience - Kennedy, Kieran Anthony (Oxford : Clarendon Press, 1971)
This book is primarily concerned with the causes of differences among manufacturing industries in the growth of labour productivity and association between long-term changes in productivity and output with special references to Irish manufacturing industry
Revision of author's thesis, Harvard.
Bibliography: p. [272]-276.
SJU 21/01/2019
Loans
Keywords: Labor productivity; Industries; Ireland